Homo Islamicus as an agent of socio-economic change: A study in the perspective of Surah An-Nisa - Amini, Salisa; Tarigan, Azhari Akmal; Syahriza, Rahmi; Ismail, Ismail (Universitas Islam Indonesia, 2024)
IntroductionThere are several challenges faced by Homo Islamicus when dealing with the conventional economic principles that often dominate economic practice today.ObjectivesThis research aims to explore the role of Homo Islamicus in creating social and economic welfare and how Islamic values can be integrated into everyday economic practices. This research focuses on the concept of Homo Islamicus as an agent of social and economic change in the context of modern society, with an emphasis on the perspective of Surah An-Nisa. MethodThe method used in this research is a qualitative analysis of the Qur'anic texts, especially Surah An-Nisa, and a literature study on the application of Islamic economic principles in a modern context. The scope of the research includes an analysis of the differences between Homo Islamicus and Homo Economicus, where Homo Islamicus is not only oriented towards material gain but also considers moral and social responsibility.ResultsThe results show that although there are challenges in applying the concept of Homo Islamicus, such as the gap between ideality and reality, this concept remains relevant as an ethical framework for building a more just and prosperous society. Homo Islamicus plays an essential role in maintaining justice in economic transactions and contributing to the welfare of society through the practice of zakat, infaq, and sadaqah.ImplicationsThe conclusion of this research confirms that sustainable social and economic welfare should be achieved. An adaptive and educative approach is needed in applying the principles of Homo Islamicus. This research recommends strengthening Islamic economic education, emphasizing social responsibility and ethics in every economic interaction.Originality/Novelty This study contributes to the body of knowledge on Homo Islamicus in the Quranic perspective as a basis for the philosophy of Islamic economics.